A fluorescent fibre solar concentrator (FFSC) design and trial run / Wang Chen - Wang, Chen (2009)
This thesis presents the author's research work on a concept development in the field of solar energy application for building illumination during his doctoral journey in Malaysia. As a considerable solution to the energy issues, solar energy is made widely available for daylighting and direct production of electricity. Various devices have been developed to collect, concentrate, transport, store and con ert solar irradiation, such as the light pipe, optical fibers, optical solar concentrators, and luminescent solar concentrators (LSC). Many limitations such a the strict dependence on beam irradiation and difficulties for wiring remain in these daylighting devices. This thesis introduces a new concept developed by the author and a new device designed and fabricated based on the concept in mitigating those limitations . The fabricated new device named "Fluorescent Fiber Solar Concentrator" (FFSC ) is a l200mm X 1200mm solar concentrator consisting of 150 piece of three-color 1m long fluorescent fibers with the diameter of 2mm. FFSC is mounted on the roof of a university building and the concentrated light is transported to a remote dark room through 10m long 2mm diameter clear optical fibers . Outdoor testing for remote indoor daylighting and power production evaluation have been conducted for the fabri cated new device FFSC. A 6-month monitored data from 24th May 2008 to 23rd Nov 2008 was analyzed.The radiation-to-radiation efficiency with a mean value of 0.057 and the lighting effect up to 114.1 lumens reveal FFSC. 'a potential in remote indoor daylighting for the application in building integration. The wavelength test and the CIE color analysis present a satisfactory match in color between the FFSC light output an the natural light.Since the sun light is free, even though the luminous efficacy as 0.6431m/W is lower than the normal electrical light sources, FFSC does not consume any electricity when operating. The light-to-light efficiency falls within the range 0.49% to 0.64% and it is expected to be raised by increasing the diameter of the fluorescent fibers embedded. FFSC systems could probably be applied for the illumination in underground areas of buildings or constructions such as the car park levels in shopping complexes, convention centers, and some office buildings. This system could also be applied to illuminate the inner areas in a building such as meeting rooms and corridors. Since electro circuits are not needed in the FFSC system, potentially FFSC systems are quite suitable for subaqueous and extremely moist operation environments when a durative illumination is needed during the daytime. Further, FFSC system do not have any risk of fire caused by the electrical current in inflammable gas conditions. .